Collective memory and narrative: ethnography of social trauma in Jammu and Kashmir - Shah, Tamanna Maqbool (Kansas State University, 2012)
Kashmir has been in the throes of a civil war since late 1989. The armed conflict between Islamist militants and the Indian security forces has consumed over one hundred thousand civilian lives. Communities have been displaced from their centuries’ old heritage. Almost every household has lost a dear one to the bullet of either a security man or a militant. Deeply entrenched patterns of militarization of the Kashmiri society encompassing a range of material and discursive processes have produced horrific social suffering for local communities in the ostensible rhetoric of protecting national sovereignty. In a situation where Kashmiris have been identified as threats to national order and incarcerated, literally and figuratively, as prisoners of the state, they try hard to retain their sense of history since awareness of history enhances communal and national identity. However, in a society under siege the only tools to retain a sense of ‘social self’ and ethnic collectivity, are through narrative telling and recall to memory that help live trauma collectively to give vent to their plight. This thesis attempts to broadly review the problem in Kashmir and then describe in detail various techniques that Kashmiri society employs like commemoration, narrative telling, oral history, symbolism, theatre, language, and memory etc. to create and live trauma collectively to maintain identity and strive for the perceived cause. Through such reliving of collective trauma societies seek their identity and reinvent their ethnicity.
Keywords: Insurgency; Islam; Kashmir; Memory; Narrative; Trauma; Sociology (0626)